2020
DOI: 10.1002/ange.201916041
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Separation of Minimum‐Boiling Azeotrope Toluene/Pyridine by Nonporous Adaptive Crystals of Cucurbit[6]uril

Abstract: The production of high purity toluene and pyridine is of significance in both industrial production and synthetic chemistry. The present protocols available to separate toluene/pyridine mixtures are several energy‐intensive distillation methods, which are not environmentally friendly and cost‐effective. Herein, we provide an energy‐efficient and simple adsorptive separation protocol using nonporous adaptive crystals of cucurbit[6]uril (Q[6]). Q[6] crystals separate pyridine from toluene/pyridine mixtures with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…154 Importantly, Huang, Yang and others have reported that MIMs and supramolecular polymers based on Q[n]s can be envisioned in practical applications such as pharmaceutical science [155][156][157] and functional material science. [158][159][160][161][162][163][164][165][166][167][168][169]…”
Section: Chem Soc Revmentioning
confidence: 99%
“…154 Importantly, Huang, Yang and others have reported that MIMs and supramolecular polymers based on Q[n]s can be envisioned in practical applications such as pharmaceutical science [155][156][157] and functional material science. [158][159][160][161][162][163][164][165][166][167][168][169]…”
Section: Chem Soc Revmentioning
confidence: 99%
“…5b). 115 CB6 crystals exhibit remarkable selectivity for pyridine up to 93% even with the volumetric ratio of pyridine to toluene being 1:100. Moreover, cucurbit [6]uril could be reused without lowering the performance efficiency.…”
Section: Cucurbiturilsmentioning
confidence: 99%
“…ii) Schematic of cucurbit [6]uril, as an absorbent for pyridine and toluene separation. 115 Reproduced with permission from Elsevier, Copyright 2020 and Wiley-VCH, Copyright 2020.…”
Section: Cucurbiturilsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] And several porous adsorbents involving in traditional zeolite and porous carbon, and newly developed metal-organic framework, cage compounds, hydrogen-bonded framework, and covalent organic frameworks have been attested to be effective for separating certain mixtures such as CO 2 /N 2 , C 2 H 2 /CO 2 , C 2 H 2 /C 2 H 4 , C 2 H 4 /C 2 H 6 , SO 2 /CO 2 , and Xe/Kr. [18][19][20][21][22][23][24] Among these separations, both isotope and isomer separation are highly desirable but extremely challenging, due to their urgent and plentiful demand and nearly identical physicochemical properties. For example, deuterium (D), an isotope isomer of H, is of prime importance in utilizing nuclear fusion reactors, whereas isomer separation such C 6 separation is of extreme importance in upgrading gasoline.…”
Section: Introductionmentioning
confidence: 99%